2019
DOI: 10.1136/heartasia-2019-011212
|View full text |Cite
|
Sign up to set email alerts
|

The influence of frailty under direct oral anticoagulant use in patients with atrial fibrillation

Abstract: BackgroundFrailty is a prognostic factor in patients with atrial fibrillation (AF). However, there is no report on the associations between frailty and clinical adverse events in patients with AF taking direct oral anticoagulants (DOAC). The factors related to the occurrence of clinical adverse events are still under discussion. Therefore, we examined the associations between frailty and clinical adverse events in patients with AF taking DOAC in daily clinical practice.MethodsWe retrospectively evaluated 240 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A number of studies have aimed at evaluating the clinical outcomes of DOAC treatment in frail older adults [51][52][53][54]. However, so far, no study has evaluated the risk-benefit profile of different DOAC dosing strategies in older adults with frailty, for instance by investigating the clinical outcomes of accurately and inaccurately dosed apixaban treatment in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have aimed at evaluating the clinical outcomes of DOAC treatment in frail older adults [51][52][53][54]. However, so far, no study has evaluated the risk-benefit profile of different DOAC dosing strategies in older adults with frailty, for instance by investigating the clinical outcomes of accurately and inaccurately dosed apixaban treatment in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] In a retrospective cohort of 240 AF patients receiving DOACs, the presence of frailty, as determined by the Rockwood scale, was associated with a threefold higher risk of major bleeding compared to non-frail status (8.3 vs. 1.8 per 100 person/years). 21 Similarly, a post-hoc analysis of the ENGAGE AF-TIMI 48 trial, which compared the DOAC edoxaban with vitamin K antagonists in patients with AF, found that the risk of major bleeding and systemic embolism increased in parallel with worsening frail status in both treatment groups. 22 Our results confirm and extend these earlier observations, showing an increased risk of bleeding in frail patients receiving DOACs for AF and VTE.…”
Section: Discussionmentioning
confidence: 99%
“…In hospitalized older adults, AF is significantly associated with FS, which increases the risk of stroke incidence, falls, mortality, symptom severity and length of hospital stay [ 35 ]. Additionally, studies have demonstrated that patients with AF who were frail had a higher mean CHA2DS2-VASc and HAS-BLED scores than those who were non-frail [ 31 , 34 , 35 , 69 ].…”
Section: Frailty Syndrome and Atrial Fibrillationmentioning
confidence: 99%